A Model Based Security Testing Method for Protocol Implementation. (3rd July 2014) - Fu, Yu Long; Xin, Xiao Long
Abstract : The security of protocol implementation is important and hard to be verified. Since the penetration testing is usually based on the experience of the security tester and the specific protocol specifications, a formal and automatic verification method is always required. In this paper, we propose an extended model of IOLTS to describe the legal roles and intruders of security protocol implementations, and then combine them together to generate the suitable test cases to verify the security of protocol implementation.